2007
DOI: 10.1128/jvi.01587-06
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mutagenic Analysis of Foot-and-Mouth Disease Virus 3C Protease Reveals the Role of the β-Ribbon in Proteolysis

Abstract: The 3C protease (3C pro ) from foot-and-mouth disease virus (FMDV), the causative agent of a widespread and economically devastating disease of domestic livestock, is a potential target for antiviral drug design. We have determined the structure of a new crystal form of FMDV 3C pro , a chymotrypsin-like cysteine protease, which reveals features that are important for catalytic activity. In particular, we show that a surface loop which was disordered in previous structures adopts a ␤-ribbon structure that is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 34 publications
8
109
0
Order By: Relevance
“…Two synthetic MCoTI-II analogues were reported to exhibit significant activity against 3C protease, a cysteine protease involved in the formation of proteins required for the RNA replication of the foot-and-mouth-disease virus (FMDV) (50,51). This report not only discovered the first peptide-based inhibitor of this agriculturally important viral enzyme, but also demonstrated that the enzyme specificity of this class of cyclotides can be redirected with simple point mutations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two synthetic MCoTI-II analogues were reported to exhibit significant activity against 3C protease, a cysteine protease involved in the formation of proteins required for the RNA replication of the foot-and-mouth-disease virus (FMDV) (50,51). This report not only discovered the first peptide-based inhibitor of this agriculturally important viral enzyme, but also demonstrated that the enzyme specificity of this class of cyclotides can be redirected with simple point mutations.…”
Section: Discussionmentioning
confidence: 98%
“…The 95% confidence intervals (95% CI) were also determined. The relative activity of lysine mutants was estimated using the IC 50 value of kalata B1 divided by the IC 50 value of mutants individually.…”
Section: Methodsmentioning
confidence: 99%
“…The active site of Lb pro with catalytic residues (Asn46, Cys51, His148, and Asp163) and some other important residues (Asn54, Gly145-His148, Asp163-Asp166) contributing to conformational changes is highlighted. (B) Structure of FMDV 3C pro C163A and the active site of the enzyme (PDB:2J92) [134]. The secondary structure of 3C pro is colored as in A.…”
Section: Non-structural Proteinsmentioning
confidence: 99%
“…pro , HRV 3C pro , and CVB 3C pro (14,18,20), but was not found in picornaviral proteases with Cys-His-Asp triads (4,5,7,21), suggesting that the hydrogen bond donated by residue Asn69 serves to further stabilize the conformation of the relatively longer glutamic acid side chain, which tends to be more flexible than the aspartic acid counterpart in Cys-His-Asp triads. However, the residue Asn69 is not strictly conserved in picornaviral 3C proteases even in PEV 3C pro , BEV 3C pro , and HRV 3C pro from a different HRV serotype (17) (Fig.…”
mentioning
confidence: 94%